New developments in round robin algorithms and their applications: A systematic mapping study - Frantz, R. Z.; Roos-Frantz, F.; Basto-Fernandes, V.; Freire, D. L. (International Journal of Business Process Integration and Management, 2022)
Enterprises have a set of applications support that needs to work synchronously and efficiently to respond quickly to business processes. To achieve high performance in the execution of the applications, software engineers suitably must use task scheduling on the computational resources. The round robin algorithm is an efficient and effective scheduling technique for task scheduling in computing. This article provides a systematic mapping study that identifies the state-of-the-art in the research of the round robin algorithms to guide researchers and practitioners in the field of software engineering. The research regarding the improvement in the round robin algorithm continues active, indicating that it remains one of the more efficient scheduling techniques in the fields of packets, CPU and virtual machine scheduling.